A Case of Hb Aalborg (HBB: c.223G>C) with Chronic Obstructive Pulmonary Disease: A First Familial Presentation in Japan. (4th March 2021) - Takamura, Kei; Komori, Taku; Hashino, Yuiko; Suzuki, Takatoshi; Shiwaku, Ai; Kikuchi, Hajime; Yamamoto, Makoto; Yamauchi, Hidetoshi; Yamashiro, Yasuhiro
Abstract: The proband was a male in his seventies who came to our facility because of shortness of breath. He was not anemic but presented dissociation between oxygen saturation (SpO2 ) and partial pressure of oxygen (PaO2 ) by blood gas analysis, and also demonstrated hemoglobinopathy after measurement of Hb A1c using high performance liquid chromatography (HPLC). Twenty-three percent of unknown hemoglobin (Hb) bands were detected. After sequencing the β-globin gene, we noted a missense mutation at codon 74 ( G GC> C GC) (Gly→Arg) of the β-globin chain and he was diagnosed with Hb Aalborg ( HBB : c.223G>C). One of the proband's siblings was diagnosed to have a low SpO2 level and also diagnosed to carry Hb Aalborg; she was also mildly anemic. This is the first known familial case of Hb Aalborg in Japan. In addition to Hb Aalborg, our case had underlying chronic obstructive pulmonary disease (COPD). Herein we present this case as a rare addition to the hematological literature.